The New Legal Empiricism & Its Application to Access-to-Justice Inquiries - Greiner, D. James (Daedalus, 2019)
The United States legal profession routinely deals with evidence in and out of courtrooms, but the profession is not evidence-based in a scientific sense. Lawyers, judges, and court administrators make decisions determining the lives of individuals and families by relying on gut intuition and instinct, not on rigorous evidence. Achieving access to justice requires employing a new legal empiricism. It starts with sharply defined research questions that are truly empirical. Disinterested investigators deploy established techniques chosen to fit the nature of those research questions, following established rules of research ethics and research integrity. New legal empiricists will follow the evidence where it leads, even when that is to unpopular conclusions challenging conventional legal thinking and practice.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE2Mi9kYWVkX2FfMDA1MzY